HAK PEKERJA PADA ADDENDUM PERJANJIAN KERJA WAKTU TERTENTU (PKWT) BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN PADA PT BENGKALIS KUDA LAUT - Rezkie Prajwalita; Rika Lestari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Employment agreement to be determined by the workers/laborers and employers must not conflict with labor agreements that have been under legislation. PKWT made between workers with PT. Bengkalis Kuda Laut addendum are discussing the amount of the basic salary and allowances, overtime wages, health care benefits, leave, legal efforts to track the settlement of industrial disputes, wage eat, granting permission. Those things are not set at the previous PKWT letter that was signed by both parties, so that the agreement between the parties was formed on the addendum at the end of the principal agreement which was signed on 28 April 2009. Based on interviews with Hendra Apriyadi as driver PT. Bengkalis Kuda Laut is known that in the addendum, that the payment of overtime, severance pay, annual leave money and money substitutes calories. Payment of overtime, severance pay, annual leave and the money is not paid by PT. Bengkalis Kuda Laut is not in accordance with the agreement. Calorie substitute money that has been set in the addendum is not feasible and is not suitable for workers. At the time of fulfillment of the right of workers experiencing barriers that appear to be caused by the workers and PT. Bengkalis Kuda Laut.Issues examined in this study are: First, How fulfillment of the rights of workers set out in the addendum PKWT under Law No. 13 Year 2003 on Manpower on PT. Bengkalis Kuda Laut? Secondly, Is the obstacles that appear on the fulfillment of the rights of workers set out in the addendum PKWT under Law No. 13 Year 2003 on Manpower on PT. BKL? Third, How does the completion of the rights of workers in the event of a dispute between the workers and PT. Bengkalis Kuda Laut?The results of this study are the First, fulfillment of the right of workers set out in the addendum PKWT not performing well because of PT. Bengkalis Kuda Laut did not fulfill its obligations. Some workers rights are not met by PT. Bengkalis Kuda Laut. Second, barriers arising from their rights and obligations are not fulfilled and the fault of one party or both parties in the agreement. Every relationship there is the potential for conflict and a source of tension between the first and second party, giving rise to disputes between the parties. Third, In a dispute over workers' rights among workers with PT. Bengkalis Kuda Laut non paths pursued litigation, precisely resolving industrial disputes in accordance with what is stated in the addendum PKWT. Workers and PT. Bengkalis Kuda Laut choose the path of industrial relations mediation.Keywords: Agreement - Addendum - PT. Bengkalis Kuda Laut